Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Pada Produk Skincare Somethinc di Kalangan Mahasiswa UBP Karawang - Puspitasari, Sekar Ayu; Darul Fadli, Uus Mohammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Today's business world is very competitive in all fields, especially in the beauty industry. With the various types of beauty products on the market, consumers are increasingly cautious in choosing the skin care they are interested in. The development of a global cosmetic and skincare business has had a significant impact on the rapid expansion of the Indonesian market. Somethinc, a local facial care business, was founded in March 2019 by Irene Ursula, a highly accomplished woman.  This study aims to test and assess the influence of product quality on consumer purchasing choices among UBP Karawang students regarding Somethinc facial care products. In this study, quantitative methodology was applied, and the sample size was one hundred people. Structural Equation Modeling (SEM) methodology was used in this study, and SmartPLS software was used to conduct the investigation. According to the results of a study conducted in 2024 by Sukawati and colleagues, product quality does not have a substantial impact on the decisions consumers make regarding their next purchase. It is true that this is the situation.